Analysis Of Work Ethics And Workload On Job Satisfaction Impact On Employee Performance - Lily Haryati; Graverra Personata; Gita Sugiyarti (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The purpose of this research is to evaluate the relationship between work ethic and workload with job satisfaction, which affects employee performance. Participants in this study consisted of 100 employees at Ngudi Waluyo University, located in Ungaran, Central Java, Indonesia. The research uses quantitative methods, with data collection carried out by filling out questionnaires. The analysis tool used is SPSS. The results show that work motivation has no significant impact on the level of job satisfaction. However, workload has a significant influence on the level of job satisfaction. On the other hand, work ethic has no effect on employee performance, and workload also has no impact on employee performance. Nonetheless, it was found that job satisfaction is related to employee performance. Keywords : work ethic, workload, job satisfaction, employee performance.